Remediation of lead contaminated soils by stabilization/solidification - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2002)
Most available remediation technologies for treatment of heavy metal contaminated soils are very expensive and result in residues requiring further treatment. Stabilization/solidification (immobilization) techniques however, which are designed to decrease leaching potential of heavy metals from soil by addition of chemical additives, provide very cost-effective solutions for heavy metal contaminated soils. This study investigates the most efficient additive for immobilization of lead. To achieve this goal, several leaching experiments were conducted for mixtures of different additives (lime, activated carbon, clay, zeolite, sand and cement) with artificially Pb contaminated (spiked) soil samples in accordance with the Toxicity Characterization Leaching Procedure (TCLP) developed by U.S. EPA. Results showed that among the additives tried, activated carbon, clay, zeolite and sand are not very efficient for Pb immobilization. On the other hand, lime and cement are significantly effective in Pb immobilization with 88% efficiency at 1:21 lime:soil ratio and 99% efficiency at 1:15 cement:soil ratio, respectively.
Keywords: contaminated soil; heavy metals; immobilization; lead; metal leaching; soil pollution; soil remediation; stabilization/solidification; TCLP